2010
DOI: 10.2174/092986610792231447
|View full text |Cite
|
Sign up to set email alerts
|

Aspartimide Modified Galanin Analogue Antagonizes Galanin Action on Insulin Secretion

Abstract: Aspartimide (Asi) formation is one of the most serious side reactions that can occur both during solid phase synthesis and storage of peptides containing aspartic acid. Although numerous studies on the mechanism of Asi formation conducted so far, the problem still remains unresolved and relatively little is known about the impact of this side reaction on biological properties of such modified peptides. In the present work we characterized the effect of Asi formation on biological properties of galanin(1-15) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…An administration of galanin inhibits basal insulin secretion in a dose-dependent manner (Manabe et al, 2003). This inhibition may be blocked by its antagonists (Olkowicz et al, 2007;Ruczyński et al, 2002Ruczyński et al, , 2010 (Tang et al, 2012). These results showed that galanin has a suppressive role in physiologic insulin secretion and that G(o)2 is a major transducer for the inhibitory regulation of insulin secretion.…”
Section: Animals Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…An administration of galanin inhibits basal insulin secretion in a dose-dependent manner (Manabe et al, 2003). This inhibition may be blocked by its antagonists (Olkowicz et al, 2007;Ruczyński et al, 2002Ruczyński et al, , 2010 (Tang et al, 2012). These results showed that galanin has a suppressive role in physiologic insulin secretion and that G(o)2 is a major transducer for the inhibitory regulation of insulin secretion.…”
Section: Animals Studiesmentioning
confidence: 97%
“…There is growing evidence indicating a suppressive role of galanin in the release of insulin from the pancreatic islets (Manabe et al, 2003;Olkowicz et al, 2007;Ruczyński et al, 2002Ruczyński et al, , 2010Tang et al, 2012). An administration of galanin inhibits basal insulin secretion in a dose-dependent manner (Manabe et al, 2003).…”
Section: Animals Studiesmentioning
confidence: 99%
“…To date, however, few papers have summarized the effect of the galanin peptide family on metabolism of glucose and resistance of insulin as yet. Galanin strongly inhibits the secretion of insulin in dogs, pigs and rats (McDonald et al 1985;Lindskog et al 1990;Manabe et al 2003;Ruczynski et al 2010;Tang et al 2012;Fang et al 2014).…”
Section: Galaninmentioning
confidence: 99%
“…Numerous animal experiments indicated a suppressive effect of galanin on insulin release from the pancreatic islets in a dosedependent manner (Ruczyński et al, 2010;Tang et al, 2012). But this inhibitive effect of galanin on insulin secretion does not interfere its beneficial role to elevate insulin sensitivity of subjects (see Table 2).…”
Section: Galanin Alleviates Insulin Resistancementioning
confidence: 99%